Performance Optimization of Microbial Fuel Cell (MFC) Using Lactobacillus bulgaricus - Arbianti, Rita; Utami, Tania Surya; Hermansyah, Heri; Novitasari, Deni; Kristin, Ester; Trisnawati, Ira (UI Scholars Hub, 2013)
Electrical energy needs in Indonesia are expected to continue to rise. The use of petroleum as a source of energy still dominates, although oil reserves in Indonesia are increasingly being depleted. Therefore, there is a need to develop alternative sources of sustainable energy, such as microbial fuel cell (MFC). In this study, Lactobacillus bulgaricus was used as an electricity producer in a dual-chamber MFC reactor. We investigated the maximum electrical energy by varying the bacterial optical density (OD), the operational time of MFC, the reactor volume, the electrolyte solution, and the configuration of MFC reactor. In this study, the maximum electrical energy (201.8 mW/m2) was generated at an OD of 0.5 in an MFC reactor series using potassium permanganate as the electrolyte solution.